Penerapan Posisi Head Up 30 Derajat terhadap Peningkatan Saturasi Oksigen pada Pasien Stroke Non Hemoragik di Instalasi Gawat Darurat RSUD Gunungjati Kota Cirebon - Wulan Dari; Muadi Muadi (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Non-hemorrhagic stroke is a neurological disorder caused by obstruction of blood flow to the brain, resulting in reduced oxygen and nutrient supply to cerebral tissue. This condition can lead to impaired cerebral perfusion, decreased oxygen saturation, and neurological dysfunction. One of the non-pharmacological interventions that can be implemented to improve oxygenation in non-hemorrhagic stroke patients is the application of a 30-degree head-up position. This intervention aims to improve cerebral venous return, optimize cerebral perfusion, and enhance oxygen saturation.This study aimed to analyze the effectiveness of the 30-degree head-up position in improving oxygen saturation (SpO₂) among non-hemorrhagic stroke patients in the Emergency Department of Gunungjati Regional Hospital, Cirebon City. The study employed a descriptive case study approach by implementing nursing interventions in non-hemorrhagic stroke patients experiencing impaired cerebral perfusion and decreased oxygen saturation. The intervention involved positioning patients in a 30-degree head-up posture while observing oxygen saturation levels before and after treatment.The findings demonstrated an increase in oxygen saturation levels following the implementation of the 30-degree head-up position. This intervention was shown to improve cerebral tissue oxygenation, stabilize hemodynamic conditions, and enhance patient comfort. Therefoe, the 30-degree head-up position can be recommended as a non-pharmacological nursing intervention for non-hemorrhagic stroke patients in emergency settings.